Corpora and the changing society studies in the evolution of English - Rautionaho, Paula; Nurmi, Arja; Klemola, Juhani (Studies in corpus linguistics ;, 2020)
"This book showcases eleven studies dealing with corpora and the changing society. The theme of the volume reflects the fact that changes in society lead to changes in language and vice versa. Focusing on the English language, be it from Old English to the present, or a shorter time span in the immediate past, the contributors in this volume use a variety of corpus methods to address the two patterns of change. The cross-fertilization of cultural studies and corpus linguistics, we hope, is beneficial for both parties, as corpus linguistics offers a vast array of materials and methods to investigate cultural and societal change, while cultural studies provide the theoretical background on which to build our research. The studies included in the present volume illustrate the potential avenues and the merits of combining changing language and changing societies"--